Orofacial granulomatosis を初発したクローン病の１例 - 大島, 麻耶; 田中, 茂男; 末光, 正昌; 久山, 佳代 (日本口腔外科学会雑誌, 2025)
Crohn's disease (CD) is a progressive, idiopathic granulomatous inflammatory disease that can affect any location of the gastrointestinal tract from the mouth to the anus. Orofacial granulomatosis (OFG) has been reported to occur as a manifestation of CD in young individuals. This report presents the case of an 11-year-old girl who was diagnosed with CD two years after the onset of OFG. Oral examination revealed diffuse enlargement of both lips and hyperplastic gingival enlargement in the anterior regions. These observations were consistent with OFG. Histopathological examination of a gingival biopsy reported the presence of noncaseating, epithelioid-type granulomas. Two years later, the patient was hospitalized for hematochezia. The diagnosis of CD was made by her gastroenterologist. After initiating biologic therapy, both intestinal and OFG symptoms went into remission. OFG may occur for a variety of reasons. Particular attention should be paid to pediatric OFG, which may precede gastrointestinal lesions. Clinicians should consider CD in the differential diagnosis.